Evaluasi Gerakan Sejuta Pengawas Pemilu Dalam Pengawasan Pemilu Tahun 2014 di Jawa Tengah - Maulana, Fanino Jati; Fitriyah, Fitriyah; Astuti, Pudji (Journal of Politic and Government Studies, 2015)
ABSTRACTEvaluation of the election monitoring movement of a milion volunteer in 2014, Central Java Â Â Bawaslu is the body responsible for supervising the elections across regions of the unitary state of the republic of Indonesia. In efforts to reduce and prevent any violation in the 2014 election, Bawaslu involving public participation for the supervision activities through Gerakan Sejuta Relawan Pengawas Pemilu (GRSPP) With this movement existence, however, the election violation keeps coming up on the 2014 election in the Central Java Province.To discover the problem and the purpose of research, researcher used a qualitative-descriptive approach. Descriptive research is itended to explore and clarify a phenomena. The purpose of this research is to analyze the activity of Gerakan Sejuta Relawan Pengawas Pemilu at central Java. The data obtained is used to formulate recommendations as a feedback toward the sustainability of GRSPP in the future in the Central Java Province.The result of this study represents that GRSPP has not been running properly in the Central Java Province on 2014. This is caused by the less of effectiveness in creatingÂ caring-society oversight the election supervision. The less quality of the volunteers in understanding to fill the report form of election violation and the violation itself is still noticeably high over the campaign phase. On the other hand, there are some purpose of this movement which has been already accomplished, such as enhance scientific repertoire and build up a fear feeling of the election candidates for committing violations.Recommendations can be given are: technical guidance and socialization by Bawaslu will Million Volunteer Movement Monitoring Election to the volunteers and the public, gave appreciation to the volunteers in the form of material and real, such as the provision of certificates to giving money when volunteers were enrolled find violations.Keywords: Evaluation, Gerakan Sejuta Relawan Pengawas Pemilu (GRSPP)